2020
DOI: 10.3906/zoo-2005-52
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide residues in feathers of four bird species from western part of Turkey

Abstract: The use of organochlorine pesticides (OCPs) has decreased considerably worldwide; they have been banned in most countries due to adverse impacts on wildlife. The purpose of the study was to investigate OCP residue levels in wild birds from Aegean, Marmara, Mediterranean, and Central Anatolia geographical regions of Turkey. Feather samples (n = 80) of four bird species in four regions were collected from anthropogenically dead birds such as roadkill and wind turbine collision. Feather samples were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The POPs affect not only aquatic animals like fish but also terrestrial animals and birds through the food web. Some researchers have stated that POP residues can reach a substantial level in birds (Arıkan et al, 2018a;Arıkan and Turan, 2020) and have suggested that their feathers can be used as a nondestructive method for terrestrial pesticide monitoring. There are only limited studies from Turkey on the effects of OCPs on birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The POPs affect not only aquatic animals like fish but also terrestrial animals and birds through the food web. Some researchers have stated that POP residues can reach a substantial level in birds (Arıkan et al, 2018a;Arıkan and Turan, 2020) and have suggested that their feathers can be used as a nondestructive method for terrestrial pesticide monitoring. There are only limited studies from Turkey on the effects of OCPs on birds.…”
Section: Discussionmentioning
confidence: 99%
“…Mammals, another vertebrate group, are also exposed to significant levels of OCP pollutants (Mason and O'sullivan, 1992;Harding, 1999;D'Have, 2006;Arıkan et al, 2018b). Other researchers have also reported that OCP residues, in particular DDTs, cause the most concerns, which include the problems of reproductive failure and declining breeding success (Arıkan and Turan, 2020;Scharenberg and Looft, 2004;Toschik et al, 2005;Corsolini et al, 2006;Hernández et al, 2008). Studies related to OCP residues in the keratinous tissue of mammals (Arıkan et al, 2018b), birds (Arıkan et al, 2018a;Arıkan and Turan, 2020;Arıkan et al, 2017;Ayaş et al, 1997), and fish (Coelhan et al, 2006) in Turkey show that DDTs are at the highest levels when compared with other congeners.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive anthropogenic impact, climate change and the subsequent transformation of natural biogeocenoses significantly alter the number of species or whole complexes and affect the restructuring of bird populations, their phenology and reproductive biology (Kuranov 2009, Arikan & Turan 2020. Birds are most sensitive to anthropogenic changes during their reproductive period.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of fumigants is problematic because of their effects on the environment and high costs. Due to the harmful effects of chemicals on humans as well as non-target organisms (Arıkan and Turan 2020), different alternative control methods are sought today. Entomopathogenic organisms are environmentally friendly control agents and suppress pest populations under natural conditions.…”
Section: Introductionmentioning
confidence: 99%